2019
DOI: 10.1101/843169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Narrative and Gaming Experience Interact to Affect Presence and Cybersickness in Virtual Reality

Abstract: Research has established a link between presence and cybersickness in virtual environments, but there is significant disagreement regarding the directionality of the relationship (positive or negative) between the two factors, and if the relationship is modulated by other top-down influences. Several studies have revealed a negative association between the factors, highlighting the prospect that manipulating one factor might affect the other. Here we examined if a top-down factor (narrative context) enhances p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…High levels of motion have consistently been shown to increase nausea, disorientation, and oculomotor disturbances [ 21 , 37 , 58 ]. Other factors such as scene complexity [ 68 ], presence [ 10 , 11 ], and locomotion [ 69 ] have also been suggested to play a role in the development of VR sickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of motion have consistently been shown to increase nausea, disorientation, and oculomotor disturbances [ 21 , 37 , 58 ]. Other factors such as scene complexity [ 68 ], presence [ 10 , 11 ], and locomotion [ 69 ] have also been suggested to play a role in the development of VR sickness.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, presence is not a prerequisite for exergames but can provide added benefits [ 9 ]. However, in VR, presence is the cornerstone of a successful virtual experience, with greater presence leading to better task performance and stronger physiological responses compared with other screen-based activities [ 10 - 12 ]. Similarly, immersion and presence in VR exergames play a major role in the motivation of users and their continued engagement [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor to consider when using VR is age, as it can influence the users' experience and perception of cybersickness (Weech et al, 2020). Previous studies have suggested that older adults may be more susceptible to cybersickness compared to younger individuals due to age-related changes in sensory and motor functions .…”
Section: Age and Cybersicknessmentioning
confidence: 99%
“…A (VR) Headset is a head-mounted device that gives virtual reality to the wearer. Virtual reality (VR) headsets are mainly used with computer games yet they are also used in different applications including test systems and coaches [9].…”
Section: Virtual Reality Headsetmentioning
confidence: 99%